1986
DOI: 10.1080/01688638608405177
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Low-Level mercury exposure and neuropsychological functioning

Abstract: To measure the effects of chronic low-level exposure to inorganic mercury, the neuropsychological performances of 13 female dental auxiliary workers with elevated head mercury levels (as measured by an X-ray fluorescence technique) were compared with 13 workers with no measurable mercury levels. Workers with elevated mercury levels scored significantly less well on the Recurrent Figures, and SCL-90-R, but not on the WAIS, Rey's AVL, PASAT, BGT, Grooved Pegboard, and Finger Tapping tests. Chronic subtoxic level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
43
1
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 28 publications
11
43
1
1
Order By: Relevance
“…31 In our study, dentists were significantly more likely than control subjects to report that they had suffered from and received treatment for a kidney disorder, but there was no observed relationship between levels of urinary mercury and reporting of kidney disorders. Vershoor et al 18 similarly reported a relatively high percentage of dental staff exhibiting renal dysfunction but found no significant relationship between urinary mercury levels and kidney disorders.…”
Section: Biological Measurementsmentioning
confidence: 57%
“…31 In our study, dentists were significantly more likely than control subjects to report that they had suffered from and received treatment for a kidney disorder, but there was no observed relationship between levels of urinary mercury and reporting of kidney disorders. Vershoor et al 18 similarly reported a relatively high percentage of dental staff exhibiting renal dysfunction but found no significant relationship between urinary mercury levels and kidney disorders.…”
Section: Biological Measurementsmentioning
confidence: 57%
“…Several studies have reported neurobehavioral effects related to motor and cognitive functions (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) in humans during ongoing exposure to mercury vapors. Contrary to the large number of studies on currently exposed workers, few epidemiologic studies have focused on the long-term effects on workers who are no longer exposed.…”
Section: Discussionmentioning
confidence: 99%
“…Neurobehavioral effects of occupational exposure have been described as falling into the 3 major groups of alterations in emotional state, effects on cognitive functions, and effects on motor functions (1,2). Ongoing exposure to lower concentrations of mercury vapors has been associated with increased hand or finger tremor, subclinical changes in coordination, neuromuscular functions, and deficits in memory and attention (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Magos (21) suggested that it may be a mistake to relate defects to exposure estimates valid at a time when the possibility of higher exposure in the past cannot be excluded.…”
mentioning
confidence: 99%
“…All studies found significant correlations between level of mercury in blood, urine, nails, hairs, or air, and results for the tests used in the respective studies (neurological, psychological, or both) [75][76][77][78][79][80][81][82][83]. One study found more physical and psychological symptoms in dentists and their personnel than in controls [84], and one single-group cross-sectional study found moderate to severe deviations from norm results of a standardized neuropsychological test-battery (memory, attention, language tasks, visuo-spatial capacity) in 17% of the tested persons and one standard-deviation from population norms for the group as a whole [85].…”
Section: Mercury Exposure In Workersmentioning
confidence: 99%